Respostas
respondido por:
5
y = (5x - 3)^-1
y' = (- 1).5.(5x - 3)^-2
y'(1) = (- 1).5.(5.1 - 3)^-2
y'(1) = (- 5).( 2 )^-2
y'(1) = (- 5)/( 2 )^2
y'(1) = - 5/4.
y' = (- 1).5.(5x - 3)^-2
y'(1) = (- 1).5.(5.1 - 3)^-2
y'(1) = (- 5).( 2 )^-2
y'(1) = (- 5)/( 2 )^2
y'(1) = - 5/4.
respondido por:
1
Resposta:
resposta letra A -5/4
Explicação passo-a-passo:
y = (1)/(5x -3)
f(x) = 1
f’(x) = 0
g(x) = 5x – 3
g’(x) = 5
y’ = [(5x – 3). 0 – 1.5]/(5x – 3)2
y’ = -5/(5x – 3)2
y’= -5/4
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás